The role of specific heat capacity on building energy performance and thermal discomfort - Muñoz, Pedro; González, C.; Recio, R.; Gencel, Osman (Case Studies in Construction Materials, 2023)
The key role of the building and construction sector, in terms of sustainability and decarbonization, has led building codes to tighten mandatory requirements related to buildings energy performance. Envelope quality, beyond light efficiency or the renewable energy contribution, is a key factor since the highest percentage of energy consumption is produced by thermal losses through enclosures. Therefore, building codes have significantly increased the mandatory benchmarks for equivalent thermal transmittance. However, the specific heat capacity (SHC) has commonly been overlooked in the discussion. Thus, in order to estimate the impact of such parameter in the energy consumption and thermal comfort of residential and non-residential buildings, a building model has been simulated by means of Transfer Functions Methods and the Finite Difference Methods. A traditional double brick façade has been considered and the SHC of bricks has been varied from 800 to 1800 kJ/kg K. The thermal behavior of the building has been assessed at several locations in accordance with the Spanish building code. In addition, building orientation has also been shifted from north to south. Although passive strategies have not been considered, the results show significant energy savings (i.e. up to 20%) and a reduction of thermal discomfort (i.e. up to 20%), depending on the type of building and its location.
Keywords: building envelope; construction materials; energy performance; specific heat capacity; thermal conductivity; Scopus; JCR